2020
DOI: 10.1080/0966369x.2020.1855122
|View full text |Cite
|
Sign up to set email alerts
|

A black man is a cornered man: migration, precarity and masculinities in Johannesburg

Abstract: Facing an ever-changing political-economic landscape marked by inequality, joblessness, and xenophobia, migrants in inner city Johannesburg are pushed towards the economic margins, or the 'corner' of life. In this precarious place, structural and everyday violence shape the daily lives and practices of men from various parts of Africa. This article examines how such men work to live up to self and societal expectations of masculinities while attempting to adjust to the socio-economic realities they face. Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…A demographic surveillance study from rural South Africa showed that 69% of the adult population cohort migrated out of the study area at least once during a 13 year follow-up period [ 22 ]. Most of these men seek employment opportunities in cities in Gauteng Province, where Johannesburg is located, and yet research describing migrants within these urban destination sites remains limited and often comes from ethnographic rather than HIV studies [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…A demographic surveillance study from rural South Africa showed that 69% of the adult population cohort migrated out of the study area at least once during a 13 year follow-up period [ 22 ]. Most of these men seek employment opportunities in cities in Gauteng Province, where Johannesburg is located, and yet research describing migrants within these urban destination sites remains limited and often comes from ethnographic rather than HIV studies [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Most of these men seek employment opportunities in cities in Gauteng Province, where Johannesburg is located, and yet research describing migrants within these urban destination sites remains limited and often comes from ethnographic rather than HIV studies. 39,40 Movement into and within South Africa, particularly from rural to urban centers, continues to rise along with the country's rapid socio-economic growth 22 and accelerating urbanization throughout the region. 41 There is a growing recognition of the need to make HIV care more accessible to migrants in order to achieve UNAIDS 95-95-95 goals.…”
Section: Introductionmentioning
confidence: 99%
“…DMS African male freedom aspirations, pursuit of “key markers of African manhood” 2 (Barker and Ricardo, 2005), and creative strategies of social recovery/rebirth (Musariri, 2021), entailed constructing a “patchwork of patriarchies”, adapted from imperial ideologies, and locally derived (Lindsay and Miescher, 2003). DMS African male quest for freedom was often also a quest for patriarchal dividend , as migrant men sought to leverage the European imperial idea that the “autonomous, self-owning individual” deserving of a freedom paper and wage contract was male (Dru Stanley, 1998: 27).…”
Section: Introductionmentioning
confidence: 99%